Molecularly Imprinted Polymer-carbon Nanotube based Cotinine Sensor. (2016) - Abbas, Yawar; Bomer, Johan; Brusse-Keizer, Marjolein; Movig, Kris; van der Valk, Paul; Pieterse, Marcel; Segerink, Loes; Olthuis, Wouter; van den Berg, Albert
Abstract: A cotinine sensor based on the dc resistance of a polymer composite films is presented. The composite film comprises a cotinine selective molecularly imprinted polymer and carbon nanotube particles. This polymer film is deposited over a gold interdigitated electrode array to measure its electrical resistance. The electrical resistance of the imprinted polymer changes upon its selective binding to the cotinine molecule. The electrical resistance increases with the increase in cotinine concentration, for the addition of 1000 ng/ml cotinine the resistance increases by ca. 190 kΩ. As a control experiment the response of un-imprinted polymer is also tested, which does not show any dependence on the cotinine concentration. Cotinine concentration in body fluid reflects the extent of tobacco smoking. This sensor has a potential to be used to detect active and passive smoking levels.